Study on Anoaâs Preference to Feed Form Under Ex Situ Conservation - Pujaningsih, RI; Sutrisno, CI; Ondho, YS; Malik, A (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
The Anoa is potential to be developed as a meat-producing animal. Â Studies on its preference to certain feed types and form is essential as an initial effort to conserve and cultivate anoa as livestock using feed processing technology. This study was aimed to evaluate the anoaâs feed preference to feed physical form, which was processed through feed processing/preserving technology. Latin square design with 3 treatments, and 3 replications was used in this study. Â The treatments were three different feed form, i.e. fresh, hay and wafers. Three anoas used as replications. Eating behaviour (eating, rumination upon standing, lying and wallowing), total feed consumptions, total dung, protein and crude fibre content of feed were observed. The results showed that the anoaâs feed in the ex situ area could be prepared in the form of wafers with protein content, crude fibre and total digestible nutrient of 8.11, 23.11 and 72.85%, respectively. Total digestible nutrients of wafer-shaped feed was higher than fresh and dry feed (72.85 vs 62.25, 60.88%). It could be recommended that wafer feed Â could be applied in anoa ex situ conservation and cultivation. (Animal Production 12(3): 150-155 (2010)Key words: Â anoa, feed preference, wafer, TDN, anoa cultivation